2018
DOI: 10.1049/iet-pel.2017.0361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inductor parasitic resistances on the voltage gain of high step‐up DC–DC converters for electric vehicle applications

Abstract: Reconfiguration, sizing and downsizing of the storage unit, in electrically propelled vehicles, are techniques that have been reported effective to improve the shelf life and performance of the storage cells. However, these solutions might decrease the rated voltage of the storage unit and therefore DC-DC converters with high voltage gain are suitable solutions to connect these low-voltage units to the motor drive, keeping a good performance of the vehicle. Moreover, parasitic resistances presented in the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
(79 reference statements)
0
23
0
1
Order By: Relevance
“…In [85] an Interleaved Boost with Integrated Winding Coupled Inductor (IBIWCI) is presented and the effect of the parasitic resistance on the voltage gain is compared to other coupled inductor boost topologies. It was found that the voltage gain of the IBIWCI suffers the least from this effect.…”
Section: Initial Design-converter Topology Selectionmentioning
confidence: 99%
“…In [85] an Interleaved Boost with Integrated Winding Coupled Inductor (IBIWCI) is presented and the effect of the parasitic resistance on the voltage gain is compared to other coupled inductor boost topologies. It was found that the voltage gain of the IBIWCI suffers the least from this effect.…”
Section: Initial Design-converter Topology Selectionmentioning
confidence: 99%
“…6 considers different cases of ratios between the parasitic resistances RL and the load Ro and proves the importance of parasitic components in HSU converters. It is possible to conclude that when the ratio between the parasitic resistances in the windings and the resistance of the load increases, the voltage gain is increasingly affected [20].…”
Section: B Operating Principlementioning
confidence: 99%
“…As a result of this topology optimization procedure, the core EE50 PC40 was selected for the case study described above. This core is much smaller than the one that was originally selected and that have been tested in previous studies [20] [22].…”
Section: B 2d Fem Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversores elevadores também possuem grande inserção em veículos elétricos fazendo parte do interfaceamento entre as fontes armazenadoras de energia (isto é, baterias, ultracapacitores e células combustível) e os motores elétricos [3], [4]. Também fazem parte dos sistemas das nanoredes e das microredes em corrente contínua (CC) [5], [6].…”
Section: Introductionunclassified